Pengaruh Motivasi Belajar Siswa Terhadap Hasil Belajar Matematika Di MI Tarbiyatul Akhlak Wedoroanom Driyorejo Gresik - Faridatul Umah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
This research aims to determine the effect of learning motivation on the mathematics learning outcomes of class IV students at MI Tarbiyatul Akhlak Wedoroanom Driyorejo Gresik. This type of research is descriptive quantitative with a correlation approach. The population in this study was all class IV MI, totaling 30 students. Data collection used was in the form of documentary interviews and questionnaires. The data collection technique used is the product moment correlation technique. The results of the research show that the influence of learning motivation on students' mathematics learning outcomes with the achievement of a correlation value (r) of 0.582 is in the strong category. For the normality test, data was obtained showing that interest in learning was 0.403 and mathematics learning outcomes were 0.312. Because these two variables are greater than 0.05, there is a significant influence between learning motivation on the mathematics learning outcomes of class IV students at MI Tarbiyatul Akhlak Wedoroanom Driyorejo Gresik